The Effectivity of Family Accompaniment For ROM Exercise Upon Elderly Post Stroke Patient With Hemiplegia - Mumpuni Mumpuni; Ani Nuraeni; Maidawilis Maidawilis; Uun Nurulhuda (Syntax Corporation Indonesia, 2022)
The number of stroke patient with average above 60 years old are in second top rank in Asia. Post stroke patient whose stay at home after hospitalization often had lack of treatment for ROM exercise by the believe of family that the exercise upon the elderly are not effective in ability of physical condition, uselless and wasting time. The purpose of this study is expected could give the description of the effect of accompaniment on family for ROM exercise upon post stroke elderly with hemiplegia whose been care in their own domestic in District of Pasar Minggu South Jakarta. The research are Quasi-experimental pre-post test with control group design. The sample of the study consist of 60 persons of family member which choose by purposive sampling as accordance as elderly with minimum of age 55 which got stroke with Hemiplegia at first time and been care in their own domestic. The result of the study shown that the mean difference are significant for motivation in control and intervention group 0,001 (p-value:0,005), significant in knowledge between control and intervention group 0,011 (p-value: 0,005), significant in ability for providing care for ROM exercise 0,006 (p-value: 0,05). Meanwhile the score of muscle strength had shown the difference between control and intervention group, although not significant statistically. As a result, family accompaniment could be able administered to the family with post stroke elderly.